(untitled) (The Review of Diabetic Studies, 2024)
Introduction: To have a health administration that is effective, operational readiness and crisis response are critical. Nursing, health security, and radiology units are important in guaranteeing patient safety, continuity of care, and effective management of emergency. The healthcare systems need to have coordinated strategies and ethical frameworks to work with emergencies. Aim: This research paper will focus on the input of nursing, health security, and radiology units towards operational readiness and crisis response in health management. It aims to find out the most important practices, challenges, and ethical issues in emergency preparedness and response. Methods: This will involve a mixed-method approach which will involve structured surveys, interviews, and observational assessments across healthcare units. Perceptions regarding readiness, interdepartmental collaboration, and effective communication will be assessed with quantitative data, whereas experiences, challenges and ethical dilemmas in the crisis will be explored with qualitative data. Findings: Early results show that the operation backbone is the nursing units, and the other aspect is health security that guarantees safety and order.and radiology gives the necessary support in terms of critical diagnosis. Interdisciplinary teamwork, ethical actions and administrative leadership facilitate the state of operational readiness. Conclusion: Strategic coordination and ethical frameworks as well as multidisciplinary collaboration are the basis of operational readiness. Enhancement of the functions of nursing, health security, and radiology departments enhances patient safety, effectiveness in responding to crisis, and resiliency of the health system overall. Constant assessment and readiness are necessary in case of a future emergency.